O orçamento como instrumento de planejamento, execução e controle: estudo de caso do plano diretor da Marinha do Brasil - Oliveira, Marcos Inoi de (2000)
The objective of this study is to verify if the Master PIan, instrument for planning, execution and control of the actions developed by the Brazilian Navy, is adjusted to the environment gIimpsed for the XXI century. Systemically, the theoretical referential on subjects, which are pertinent to the problem to be investigated, is constructed, such as the decision theory, budgetary theory, strategic management and theoretical models for planning and control systems. The result of the analysis of the features of the system and the process of the Master Plan indicates that there are points to be perfected. To the end, a summary of suggestions of measures is offered, in order to beco me the Master PIan an up-to-date instrument for budgetary management.